Man on a ledge [videorecording (DVD)] - Leth, Asger; Worthington, Sam, 1976-; Banks, Elizabeth, 1974-; Bell, Jamie, 1986-; Mackie, Anthony, 1978-; Sedgwick, Kyra; Harris, Ed, 1950- (Summit Entertainment, 2012)
"Ex-cop Nick Cassidy ... escapes from prison to plan the ultimate heist: steal a $40 million diamond from cutthroat businessman David Englander..., and in the process prove his own innocence. From the ledge of the famous Roosevelt Hotel with the whole world watching, Cassidy plays a clever game of cat and mouse with the NYPD while his dutiful brother Joey ... races against the clock to extract the diamond and clear his brother's name"--Container.